2005
DOI: 10.1007/s00198-005-1933-1
|View full text |Cite
|
Sign up to set email alerts
|

Bone status of Indian women from a low-income group and its relationship to the nutritional status

Abstract: Indian women from low-income groups consume diets that have inadequate calcium coupled with too few calories, proteins and micronutrients. Hospital-based data suggest that these women have osteoporotic hip fractures at a much earlier age than Western women. Studies reporting bone parameters of the Indian population involving large sample sizes are not available. This study was therefore carried out with 289 women in the 30-60-year age group to estimate the prevalence of osteoporosis and measure the bone parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
94
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 21 publications
7
94
2
1
Order By: Relevance
“…This finding is similar to the one in our study except the fact that urban slum population is a mixture of people from different locality thus showing the minor variations. 7 In a report published by Vinay Kumar et al, in the year 2012, the nutritional status of Indian women is inadequate: 33% of married women (aged 15-49 years) are too thin (i.e., BMI <18·5 kg/m 2 ). This is in contrast to the findings from our study which found 14.3% of women in the reproductive age group having BMI below 18.5kg/mt 2 .…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to the one in our study except the fact that urban slum population is a mixture of people from different locality thus showing the minor variations. 7 In a report published by Vinay Kumar et al, in the year 2012, the nutritional status of Indian women is inadequate: 33% of married women (aged 15-49 years) are too thin (i.e., BMI <18·5 kg/m 2 ). This is in contrast to the findings from our study which found 14.3% of women in the reproductive age group having BMI below 18.5kg/mt 2 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the RDA for calcium has not been established for menopausal women in India subsisting on a cereal-pulse diet, and therefore 400 mg/day of RDA for calcium is indicated. 12 The major part of this calcium intake came from plant sources, which are known to have low bioavailability. The foods rich in calcium such as milk, spices and dry fruits are expensive and not well available for majority of this population.…”
Section: Discussionmentioning
confidence: 99%
“…The variations from the present study in incidence of osteoporosis and osteopenia by both calcaneal QUS and DEXA methods have been shown in Table 4. (11) Digital X-ray radiogrammetry 50% -Above age 50 years Shatrugna et al (12) DEXA Prevalence 29% -…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13] but still the data is scanty, particularly from this region. Hence, the present pilot study was planned to screen bone status of healthy urban women above age of 25 years (when peak bone mass is formed) from this region utilizing calcaneal QUS (Hologic Sahara 0058 USG) as a diagnostic tool.…”
Section: Introductionmentioning
confidence: 99%